The Legal Vacuum Of Interreligious Marriage In Indonesia: The Study Of Judges’ Consideration In Interreligious Marriage Court Decisions 2010 -2021 - Andra Noormansyah; Umar Haris Sanjaya (Prophetic Law Review, 2022)
There are a legal vacuum and contradictory provisions in the Marriage Law, which states that it is not permissible for an Indonesian citizen to have an interreligious marriage. It has been requested for judicial review through the Decision of the Constitutional Court No. 68/PUU-XII/2014. Article 2 paragraph (1) of Law No. 1 of 1974 on Marriage stated that marriage is legitimate if the parties concerned have similar religions and beliefs. Moreover, it has become more obvious through judicial review of the Decision on Indonesian Constitutional Court Number 68/PUU-XII/2014, which decided that Article 2 paragraph (1) Law No. 1 of 1974 which amendment by Law No. 16 of 2019 required similarity in religions and beliefs of the marriage concerned parties are not necessary to do a judicial review. On interfaith marriage, the application proved that the judge on the district court’s decisions stated that Law No. 1 of 1974 on Marriage is not regulated, not emphasized, and not containing regulation of any sort about interfaith marriage. It’s proven in most judges’ court considerations of interreligious marriage around 2010 – 2021. This study takes two research formulations such as how a legal vacuum in interreligious marriage happens and how the judges in the court consider the law of interreligious marriage. This research uses a normative method which uses a conceptual and law approach. This research results that judges always consider interreligious marriages as a legal vacuum, it happened because the law that marriages do not clearly determine textually in law no. 1 of 1974. Therefore, even if clarified by Constitutional Court is clearly but practically interpreter different by judges in district court.Keywords: legal vacuum, interreligious marriage, not emphasized, court decision Kekosongan Hukum Perkawinan Beda Agama Di Indonesia: Kajian Tentang Pertimbangan Hakim Dalam Putusan Pengadilan Perkawinan Beda Agama 2010 -2021 AbstrakAdanya kekosongan hukum dan ketentuan yang kontradiktif dalam UU Perkawinan yang menyatakan bahwa warga negara Indonesia tidak boleh melakukan perkawinan beda agama. Telah dimintakan uji materil melalui Putusan Mahkamah Konstitusi Nomor 68/PUU-XII/2014. Pasal 2 ayat (1) Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan menyatakan bahwa perkawinan sah apabila yang bersangkutan mempunyai kesamaan agama dan kepercayaan. Apalagi, hal itu semakin nyata melalui uji materil Putusan Mahkamah Konstitusi Republik Indonesia Nomor 68/PUU-XII/2014 yang memutuskan Pasal 2 ayat (1) UU No 1 Tahun 1974 yang diubah dengan UU No 16 Tahun 2019. syarat kesamaan agama dan kepercayaan dari pihak yang bersangkutan dalam perkawinan tidak perlu dilakukan uji materiil. Tentang perkawinan beda agama, permohonan tersebut membuktikan bahwa hakim pada putusan pengadilan negeri menyatakan bahwa Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan tidak diatur, tidak ditekankan, dan tidak memuat pengaturan apapun tentang perkawinan beda agama. Hal ini terbukti pada sebagian besar pertimbangan hakim terhadap perkawinan beda agama sekitar tahun 2010 – 2021. Kajian ini mengambil dua rumusan penelitian yaitu bagaimana terjadi kekosongan hukum dalam perkawinan beda agama dan bagaimana hakim di pengadilan mempertimbangkan hukum perkawinan beda agama. Penelitian ini menggunakan metode normatif yang menggunakan pendekatan konseptual dan hukum. Hasil penelitian ini bahwa hakim selalu menganggap perkawinan beda agama sebagai kekosongan hukum, hal itu terjadi karena undang-undang perkawinan tidak secara jelas menentukan secara tekstual dalam undang-undang no. 1 Tahun 1974. Oleh karena itu, kalaupun diklarifikasi oleh Mahkamah Konstitusi secara jelas tetapi secara praktis penafsirnya berbeda dengan para hakim di Pengadilan Negeri.Kata Kunci: kekosongan hukum, perkawinan beda agama, tidak ditekankan, putusan pengadilan